2003
DOI: 10.1016/s0048-7333(02)00101-4
|View full text |Cite
|
Sign up to set email alerts
|

Startup size and the mechanisms of external learning: increasing opportunity and decreasing ability?

Abstract: An important area of investigation in the field of entrepreneurship examines how people and organizations exploit technological opportunities. Prior research suggests that alliances, the mobility of experts, and the informal mechanisms associated with geographic co-location can present firms with useful opportunities to source technological knowledge. This paper uses insights from strategic management and organizational theory to suggest that organizational size may have an important impact on the extent of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
172
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(187 citation statements)
references
References 45 publications
(31 reference statements)
8
172
0
3
Order By: Relevance
“…Knowledge accessing from external organizations is considered to have become increasingly important to entrepreneurial firms, which often cannot generate internally all the knowledge necessary for innovation (Freel 2000a;Hite and Hesterly 2001;Yli-Renko et al 2001;Almeida et al 2003;Huggins and Johnston 2009;Doran et al 2012). Within an entrepreneurial firm environment, the role of inter-organizational networks and knowledge sources are recognized as potentially important assets for creating and sustaining innovation and competitiveness (Lechner and Dowling 2003).…”
Section: Network Knowledge Spillovers and Regional Innovationmentioning
confidence: 99%
“…Knowledge accessing from external organizations is considered to have become increasingly important to entrepreneurial firms, which often cannot generate internally all the knowledge necessary for innovation (Freel 2000a;Hite and Hesterly 2001;Yli-Renko et al 2001;Almeida et al 2003;Huggins and Johnston 2009;Doran et al 2012). Within an entrepreneurial firm environment, the role of inter-organizational networks and knowledge sources are recognized as potentially important assets for creating and sustaining innovation and competitiveness (Lechner and Dowling 2003).…”
Section: Network Knowledge Spillovers and Regional Innovationmentioning
confidence: 99%
“…In a foundational study on network relationships, Birley (1985) concluded that informal and formal network relationships offer varied benefits. It has also been posited that learning is dependent upon the informal versus formal mechanisms that exist (Almeida et al, 2003). Anand et al (2002) further argue that exposure leveraged from informal and formal sources differs in its content and accessibility and that firms need to "continuously monitor the quality of knowledge derived" from different sources (p. 87).…”
Section: International Exposure Through Network Relationshipsmentioning
confidence: 99%
“…First, although pioneering research on entrepreneurial networks has long recognized the differential benefits of informal versus formal networks (Birley, 1985), the implications of network relationship formality for internationalization have not yet been explored. This is rather surprising as learning has been found to be largely dependent upon the informal versus formal mechanisms that exist (Almeida et al, 2003 andAnand et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies drawing on ethnographic research as well as patent citation data have demonstrated that: 1) ideas travel across organizations more readily when they are co-located; 2) the size and mobility of the scientific labor force increase local information sharing; and 3) strategic alliances among co-located firms augment the stock of common knowledge (Saxenian, 1994;Almeida and Kogut, 1999;Almeida et al, 2003 But diversity alone is not the whole story. Depth and quality are critical too.…”
Section: ) Origins: Geographic Propinquitymentioning
confidence: 99%